The value of Stilbestrol in beef cattle rations-Wintering, grazing, and fattening phases. - Richardson, D.; Smith, E.F.; Cox, R.F.; Baker, F.H. (Kansas Agricultural Experiment Station, 2011)
Stilbestrol, a synthetic compound which has a hormonelike effect when taken into the body, has been recognized as a growth-stimulating factor in beef cattle fattening rations. Most of the market cattle in Kansas are handled under the deferred system of feeding. Information was needed on the value of this growth-stimulating ingredient in the deferred cattle-feeding program. This experiment was planned to obtain information on the value of stilbestrol (1) in the wintering ration of beef calves, (2) during grazing, (3) effect of removing stilbestrol from the animals while grazing, (4) when animals return to the feed lot after grazing, (5) effect of long-time continuous feeding, (6) effect upon digestibility of feed, (7) carcass grade, and (8) cooking quality of the meat. The results of the wintering phase are repeated in Table 30. For more complete details on this and the digestion studies, see the 4 2nd Annual Livestock Feeders' Day Report, Kansas Agricultural Experiment Station. Circular 320, pages 50-53, 1955.
Keywords: Beef; Stilbestrol; Gain